The Relationship Between Digital Marketing of Brand X and Purchase Interest - Putri, Ratu Natasya Alyssia; Ayuningtyas, Nurina; Jubaedah, Lilis (Borong Newinera Publisher, 2025)
This study aims to examine the relationship between digital marketing of Brand X and the purchase intention of female students participating in the 2024 Indonesian International Student Mobility Awards (IISMA) vocational program who studied in the United Kingdom. Brand X is a UK-based cosmetic brand that actively utilizes various digital marketing channels, including social media, websites, search engine optimization, pay-per-click advertising, affiliate marketing, and online public relations. This research employs a quantitative approach with data collected through questionnaires distributed to 37 respondents. The analysis was conducted using the Spearman correlation test since the data did not follow a normal distribution. The results show a strong and significant positive relationship between digital marketing and purchase intention, with a correlation coefficient of 0.630 and a significance value below 0.001. Additionally, the coefficient of determination indicates that 39.69 percent of the variance in purchase intention is explained by digital marketing. These findings suggest that higher perceptions of Brand X's digital marketing are associated with higher purchase intention among the IISMA students in the United Kingdom.